The Architectural Drawing Course : The Hand Drawing Techniques Every Architect Should Know - Zell, Mo (Thames & Hudson drawing series, 2017)
This comprehensive guide covers essential hand drawing techniques for architects. The book provides practical instruction on creating detailed and accurate architectural drawings, emphasizing the importance of hand skills in digital times.